The effects of digital care pathways on the healthcare professionals’ processes in specialized health care - Tuomikoski, Kirsi; Liljamo, Pia; Reponen, Jarmo; Kanste, Outi (Finnish Journal of eHealth and eWelfare, 2022)
In health care, there are more and more electronic health care services supporting patients’ self-care that enable their active participation in care. With the increase in self-care services, new e-health services are also part of the daily lives of professionals, affecting work and the content of work and changing the healthcare processes of professionals. The healthcare processes of professionals are interactive processes in relation to patients as well as expert work. The subject of the study are the digital care pathways of Health Village, a self-care service used in specialized health care. The purpose of the study is to describe the effects of digital care pathways on the healthcare processes of specialized health care from the professionals’ point of view. The study was conducted with thematic interviews with professionals using digital care pathways in four university hospitals. The informants were health care professionals from four university hospitals (n=11). Data was collected during autumn 2019 and summer 2020. A large proportion of the informants were nurses (n=8). Others participating in the study (n=3) worked as a physician, rehabilitation counselor and nutrition therapist. Data was analyzed by theory-guided content analysis. The results show that digital care pathways influenced the collaborative interaction between professionals and patients by changing the patient-professional interaction and increasing patient orientation and patient involvement. In specialized health care, the nature of the tasks of the professionals was altered. The processes became more diverse, and work was redesigned as new methods could be used in the work. Based on the results, the competence of health care professionals developed, and the competence needs of work tasks were renewed. Digital care pathways were estimated to increase the planning of time use as the division of labor changed and the use of working time became more efficient. In conclusion, digital care pathways changed the processes of health care professionals. The interaction between the professional and the patient and the nature of the tasks to be performed changed in the processes. The division of labor and the use of working time became more efficient. The results can be utilized in the design of electronic health services.